Smart cities and cumulative effects on fundamental rights - Athena Christofi (Internet Policy Review, 2023)
Smart cities are rarely built smart from scratch. For most cities, 'smart city' signifies the presence of several smart city projects that emerge over time from various actors. These projects rely on extensive data and algorithms whose use in urban spaces and/or decision-making processes can impact the enjoyment of fundamental rights in cities. Spatially-grounded and socio-economic rights may be particularly affected. This paper explores the issue of cumulative effects on fundamental rights that may arise from the gradual accumulation of smart city projects in modern cities. It argues that in such a complex landscape of multiple actors, projects and rights, important fundamental rights impacts may be incremental and inconspicuous, and thus, difficult to detect and to stop. It advocates for a fundamental rights-oriented impact assessment process that would enable local authorities to understand and mitigate cumulative effects on fundamental rights. Drawing from the environmental law area and the examples of Cumulative Effects Assessments and Strategic Environmental Assessments therein, it provides concrete recommendations for smart city stakeholders on the essential elements needed for such a process.
Keywords: 300; Smart cities; Fundamental rights; Human rights; Impact assessment; Cumulative effects